Membangun Brand Trust, Brand Preference dan Brand Equity Terhadap Niat Membeli Produk - Wahyudi, Septian; Meirina Suri, Dia; z, Syafaruddin; Munir, Abdul; Rahma Yuli, Annisa; Khairunnisa, Elma (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service activity was motivated by the low level of understanding among micro business actors in building brand strength, which has an impact on low consumer purchase intention. The main objective of this activity was to improve the knowledge and capabilities of the community in developing brand trust, brand preference, and brand equity in order to increase product purchase intention. The activity was conducted with the Program Keluarga Harapan Sekuntum Bunga group in Pekanbaru City, consisting of micro-entrepreneurs with home-based businesses. The implementation method applied a participatory and educational approach through several stages, including preparation, socialization, training, mentoring, and interactive discussion. Evaluation was carried out using a quantitative approach through pre-test and post-test as well as Likert-scale questionnaires to measure changes in participants’ understanding and perceptions of the studied variables. The results showed that out of a total of 18 participants, most experienced an improvement in their understanding of branding concepts. Approximately 72% of participants were able to create or improve their product brand identity, while the level of active participation exceeded 80%. The analysis results indicated that brand trust and brand preference had a positive and significant effect on purchase intention, whereas brand equity did not show a significant effect. The benefits obtained by participants included improved ability to build brand identity, apply simple marketing strategies, and increased confidence in promoting their products. In conclusion, strengthening brand trust and brand preference is a key factor in increasing purchase intention in micro businesses and represents an effective approach for community empowerment through marketing-based interventions.